ANALISIS PENGARUH KECEPATAN PROSES PENERIMAAN BARANG, AKURASI PROSES PENERIMAAN BARANG, KUALITAS PENERIMAAN BARANG TERHADAP EFISIENSI OPERASIONAL DI HOTEL INFINITY 8 BALI - Pratikto, Aryo; Purwanto, Edi; Ambarwati, Retnoning (ITB AAS Indonesia Surakarta, 2025)
The research problem in this study is whether the speed of the goods receiving process (X1), the accuracy of the goods receiving process (X2), and the quality of the goods received (X3) have partial and simultaneous effects on operational efficiency at Hotel Infinity 8 Bali. This study aims to analyze the influence of the speed, accuracy, and quality of the goods receiving process on operational efficiency at Hotel Infinity 8 Bali. The method used is quantitative with a multiple linear regression approach. The t-test results show that all three independent variables have a partial effect on operational efficiency, with each calculated t-value being greater than the critical t-value (speed: 6.990; accuracy: 5.212; quality: 2.915 > 1.66). Simultaneously, the F-test results indicate a significant influence of the three variables on operational efficiency, with a significance value of 0.000 < 0.05 and an F value of 132.714 > the critical F value of 3.114. The linear regression test also shows that all variables have positive coefficients, indicating that any increase in the speed, accuracy, and quality of the goods receiving process will enhance the operational efficiency of Hotel Infinity 8 Bali.